Clinical experiences of intervention of neurodevelopmental disorders and difficulties in school learning from historical-cultural neuropsychology - Bonilla-Sánchez, María del Rosario (Frontiers in Education, 2024)
Cultural Historical Neuropsychology proposes the qualitative analysis of neurodevelopmental disorders and learning difficulties, through the identification of the neuropsychological factor that underlies the symptoms and difficulties that arise in cognition an academic performance. The objective of this article is to present clinical experiences of neuropsychological intervention of unique cases of varying degrees of initial education. Qualitative assessment is a process that reveals the strengths and weaknesses in child development, as well as the possibilities of what children will be able to do for themselves, their zone od proximal development, and not just the zone of current development.Neurodevelopmental and learning disorders presents particular manifestations during life, so qualitative analysis can account for their subtle changes during the course of life and schooling. The use of the principles of intervention constitutes the methodological axis for the elaboration of the programs, these will be shaped according to the needs of the children. The case study strengthens the expertise of clinical knowledge by contributing to the empirical field on the possibilities and proposals of neuropsychological intervention.